Aqueous ionic liquid solutions for boiling heat transfer enhancement in the absence of buoyancy induced bubble departure. (July 2018) - Kumar, Nirbhay; Raza, Md. Qaisar; Seth, Debabrata; Raj, Rishi
Graphical abstract: Highlights: First pool boiling study with aqueous ionic liquid (IL) solution. A passive bubble departure mechanism on an inverted heater demonstrated. Critical heat flux (CHF) mechanism on an inverted heater explained. A maximum heat flux of 950 kW / m 2 dissipated on an inverted heater. IL solutions have the potential to significantly enhance CHF in zero gravity. Abstract: Advantage of high heat transfer during boiling is lost due to the absence of buoyancy induced bubble departure in space. Absence of bubble departure with pure water on an inverted heater in earth gravity ( - 1 g ) resembles boiling behavior in space and is often used to mimic zero-gravity ( 0 g ) boiling experiments on earth. Here we perform experiments on an inverted heater to show that unlike water, the aqueous solution of surface active ionic liquid (IL) avoids coalescence to form multiple small bubbles with significantly large wet area on the heater surface. The force of repulsion due to the interaction of ILs adsorbed at the liquid–vapor interface of neighboring bubbles induces a completely passive bubble departure away from the inverted heater surface against the combined effect of buoyancy and surface-tension. Resulting rewetting of the heater surface increases the critical heat flux (CHF) to ≈ 950 kW / m 2, which is an enhancement of ≈ 4.5 × in comparison to pure water. Effect of bulk liquid subcooling and concentration on pool boiling CHF are extensively investigated. The mechanism of CHF is explained with the help of the adsorption dynamics of IL at the solid–liquid and liquid–vapor interface of bubbles.